2017
DOI: 10.1007/s10044-017-0593-z
|View full text |Cite|
|
Sign up to set email alerts
|

Detection and classification of vehicles from omnidirectional videos using multiple silhouettes

Abstract: To detect and classify vehicles in omnidirectional videos, we propose an approach based on the shape (silhouette) of the moving object obtained by background subtraction. Different from other shape-based classification techniques, we exploit the information available in multiple frames of the video. We investigated two different approaches for this purpose. One is combining silhouettes extracted from a sequence of frames to create an average silhouette, the other is making individual decisions for all frames a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…olarak ayrılmıştır. [5]'te ise, dışbükey-lik, uzanım, dikdörtgensellik ve Hu moment öznitelikleri çıkarılarak motosiklet, araba ve dolmuş ayırt edilmiştir. HOG öznitelikleri ile tümyönlü kameralarda nesne bulmaya örnek olarak HOG hesabı tümyönlü kameralara matematiksel olarak uyarlanarak yaya, araba ve dolmuş tespiti yapılmıştır [6], [7].…”
Section: Gi̇ri̇ş Tümyönlü Kameralar Yatay Eksende 360unclassified
“…olarak ayrılmıştır. [5]'te ise, dışbükey-lik, uzanım, dikdörtgensellik ve Hu moment öznitelikleri çıkarılarak motosiklet, araba ve dolmuş ayırt edilmiştir. HOG öznitelikleri ile tümyönlü kameralarda nesne bulmaya örnek olarak HOG hesabı tümyönlü kameralara matematiksel olarak uyarlanarak yaya, araba ve dolmuş tespiti yapılmıştır [6], [7].…”
Section: Gi̇ri̇ş Tümyönlü Kameralar Yatay Eksende 360unclassified
“…In a previous study, we showed that using multiple frames of a video has a better classification performance than using a single silhouette in a single frame [19]. Among a few approaches of using multiple silhouettes, 'average silhouette' was the best performing one.…”
Section: Silhouette Extraction In Omnidirectional Videosmentioning
confidence: 99%
“…In one of our previous studies with omnidirectional cameras [19], we detect each vehicle type separately using shape features extracted from the foreground silhouettes.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies of omnidirectional cameras have examined topics such as object recognition in omnidirectional images, coding of omnidirectional images, and combining omnidirectional images [14][15][16][17][18][19][20][21][22][23][24][25][26][27][32][33][34][35][36][37]. In one example of research on object recognition using omnidirectional cameras, Premachandra et al [35] proposed a moving object detection system for road intersections and demonstrated the advantages of using omnidirectional cameras for traffic surveillance.…”
Section: Introductionmentioning
confidence: 99%